Iron (II) and zinc (II) chelating abilities of peptides from spent brewer’s yeast - Ngoc Ha, Thi Bich; Dam, Thuy Hang; Phuong Tran, Thi Lan; Hanh Tran, Thi Hong; Anh To, Kim; Anh Pham, Tuan; Le, Tuan (Academia Journal of Biology, 2026)
Zinc and iron are essential microelements that contribute to a wide range of physiological functions in humans and animals. However, their inorganic forms often have low solubility and bioavailability and leading to zinc and iron deficiency. The alternative chelated forms of these essential metals offer a high absorption rate and bioavailability of these two metals in humans and animals. Spent brewer’s yeast is considered a low-cost by-product of the brewing industry that contains high concentrations of proteins and can be used to generate zinc and iron-peptide chelate as value-added products. The purpose of this study was to investigate the potential of chelating zinc and iron using peptides resulting from spent brewer’s yeast. Our results showed that protein concentration and degree of hydrolysis increased the zinc and iron chelating ability. The peptide fraction of less than 3 kDa demonstrated a maximum chelating yield exceeding 80% at pH 7. FTIR analysis revealed that the possible chelating site might be at the C=O of the carboxyl group and the C-N or N-H of amide-I and amide-II groups.